Estimating wastewater dilution using chemical markers and incomplete flow measurements: Application to normalisation of SARS-CoV-2 measurements - Owen D. Jones; Amy J. Baldwin; Isabelle Durance; William B. Perry; Andrew Weightman (Journal of Water Process Engineering, 2026)

Noisy neighbours take their toll, especially if you are a pupfish - William Bernard Perry (Journal of Fish Biology, 2026)

Island or just island‐like? It makes a big difference to pike population structure - William Bernard Perry (Journal of Fish Biology, 2026)

Reaching gender parity and improving internationalisation after five decades of FSBI symposia, but subtle career‐stage effects on timekeeping remain - Joshka Kaufmann; William Bernard Perry (Journal of Fish Biology, 2026)
We analysed 57 years of Fisheries Society of the British Isles (FSBI) symposia, showing speakers with traditionally female names increased from near absence to reaching parity in recent symposia. International affiliations increased in the late 1980s, peaking in 2024 with 27 countries, albeit with overrepresentation of high‐income countries. Timekeeping for 68 presentations at the 2025 symposium showed that senior scientists were more likely to overrun than junior presenters; no systematic gender differences were detected. Although gender representation has improved, timekeeping asymmetries reveal career‐stage effects, underscoring the need for consistent data collection, moderation and equitable session management.

The onward march of the invasive pink salmon ( Oncorhynchus gorbuscha ) and what it means for the North Atlantic's freshwater ecosystems - William Bernard Perry (Journal of Fish Biology, 2026)

Finding needles in a haystack: measuring ambient concentrations of naturally occurring elongated mineral particles in an urban environment - Anushka Elangasinghe; Hamesh Patel; Kim N. Dirks; Wenxia (Wendy) Fan; Araliya de Zoysa; Cindy Z. Yi; Paul G. Young; Ayrton Hamilton; Nick Talbot; Martin Brook; Brett Wells; David E. Williams; et al. (Chemosphere, 2026)

A murder mystery on a catchment scale: Death by flesh eating bacteria or invasive piranha? - William Bernard Perry (Journal of Fish Biology, 2026)

How well do you know your shoalmate? The answer could be life or death - William Bernard Perry (Journal of Fish Biology, 2026)

Open Questions on Ion–Neutral Collisions and Coupling in the Lower Thermosphere–Ionosphere: Electrodynamics, Energetics and Dynamics - Theodoros E. Sarris; Stelios Tourgaidis; Dimitrios Baloukidis; Maxime Grandin; Astrid Maute; Robert F. Pfaff; Jeffrey Thayer; James Clemmons; Karl Laundal; Hanli Liu; Panagiotis Pirnaris; Noora Partamies; et al. (Surveys in Geophysics, 2026)
The Lower Thermosphere–Ionosphere (LTI) is the interface region between the Earth’s atmosphere and space. It is modulated by the energy and momentum deposition from the magnetosphere above and by the impacting waves from the lower atmosphere. The LTI region is defined by the co-existence and interaction of neutral and ionized species within the region’s electric and magnetic fields. This interplay results in unique and complex interactions between neutrals and plasmas, that are not fully understood and quantified to this date. In this paper we present an overview of some of the most important open questions related to ion/neutral coupling and the resulting collisional electrodynamics, collisional energetics and collisional dynamics processes. We outline the key reasons for addressing these questions, and highlight methodologies that can lead to their closure in the upcoming years.

Climate change linked to infertility in well‐known shark species - William Bernard Perry (Journal of Fish Biology, 2026)

National-scale river water quality in the Philippines: establishing baselines in a mineralised megadiverse nation - Emma Biles; Richard David Williams; Decibel Faustino-Eslava; Loucel Cui; Francis Ian Gonzalvo; Kim Bryan Cabrera; Manilyn Casa; Craig MacDonell; Maria Regina V. Regalado; Laura Quick; Justine Perry Domingo; Trevor Hoey; et al. (Science of The Total Environment, 2026)

What big eyes you have! Well, until 500 m, that is - William Bernard Perry (Journal of Fish Biology, 2026)

Social and Ecological Context Shape Biological Invasions in Complex Landscapes - George L. W. Perry; James M. R. Brock; Cameron B. Guy; Casey Hamilton; Finnbar Lee; Dion L. Pou; Elizabeth Williams; Erica A. H. Smithwick (Current Landscape Ecology Reports, 2025)

Use of mercury in mining 125 years ago continues to impact waterfowl populations: Implications for current artisanal gold mining - Morgan A. Byrne; Mae Sexauer Gustin; Chris A. Nicolai; Perry J. Williams (Science of The Total Environment, 2025)

Toxic tiddlers? Mechanisms driving within species mercury levels uncovered in anchovies - William Bernard Perry (Journal of Fish Biology, 2025)

Genome-resolved metagenomics uncovers antimicrobial resistance gene carriers in hospital and municipal wastewater environments - Reshma Silvester; Gordon Webster; William B. Perry; Kata Farkas; Laura Rushton; Noel Craine; Gareth Cross; Peter Kille; Andrew J. Weightman; Davey L. Jones (Science of The Total Environment, 2025)

Stress‐linked morphological change associated with rearing techniques of hatchery‐reliant endemic landlocked Atlantic salmon ( Salmo salar m. sebago ) - Aurora Hatanpää; Hannu Huuskonen; Jorma Piironen; Raine Kortet; William Bernard Perry (Journal of Fish Biology, 2025)
Domestication effects caused by hatchery rearing impact various traits in fishes. Lake Saimaa landlocked salmon ( Salmo salar m. sebago ) have been dependent on hatchery propagation for over 50 years. The population is therefore at risk of hatchery‐induced phenotypes, which can be suboptimal in the wild, thus impacting the long‐term viability of the already critically endangered population. To assess the impact of rearing techniques, one‐summer‐old landlocked salmon morphology and asymmetry (an indicator of stress) was compared between four different hatchery rearing backgrounds, with all fish originating from the same family groups. The first group was maintained under standard hatchery conditions, the second under enriched rearing conditions (varying water level, direction and velocity), the third in semi‐natural hatchery conditions (outdoor stream ponds and natural prey) and the fourth group experienced wild conditions (stocked in the River Ala‐Koitajoki as alevins in spring and electrofished in September). Fish were photographed from both left and right sides and morphology was compared between rearing types using classical linear measurements as well as geometric morphometrics. Results indicate that natural conditions produce more symmetrical fish that have longer pectoral fins than their hatchery conspecifics, whereas fish reared in semi‐natural conditions show increased asymmetry. These results suggest that different rearing types elicit varying levels of stress, and that conservation efforts encouraging early‐stage stocking in the wild could be recommended when natural reproduction is not possible.

Travelling in the omics time machine part II : Keeping natural history museums relevant - William Bernard Perry (Journal of Fish Biology, 2025)

Gaseous carbon dioxide removal from composting of biomass and cotton textile waste - Ethan Woods; Perry Berlin; Jesse Daystar; William Joe Sagues (Waste Management, 2025)

Quantitative insights into the spatio‐temporal variation of Atlantic salmon ( Salmo salar ) biomass in a river catchment using eDNA metabarcoding - William Bernard Perry; Nigel Milner; Ifan Bryn Jâms; Mark de Bruyn; Steve J. Ormerod; Kristy Deiner; Holly M. Bik; Gary Carvalho; John Colbourne; Bernard Jack Cosby; Isabelle Durance; Simon Creer (Journal of Fish Biology, 2025)
Effective species conservation and management requires comprehensive biomonitoring, enhanced by combining traditional and newer methodologies, such as environmental DNA (eDNA) analyses. A seasonal pulse of spawning adult Atlantic salmon ( Salmo salar ) was detected by normalised eDNA 12S reads from metabarcoding, which facilitated estimation of spatial patterns in salmon biomass. A strong relationship was found between normalised reads in the lower section of the River Conwy (Wales, UK) and whole‐river adult biomass (estimated from rod catch data and a fish counter), explaining 61% of the variation in a linear regression. Moreover, the positive linear relationship between adult biomass and partial effect on normalised reads occurred after the biomass estimate exceeded 1500 kg, indicating a threshold where normalised reads become representative of biomass. The relationship observed between normalised reads and biomass, as well as the unique profiles of normalised reads at each of the sites, supports the hypothesis of limited eDNA transport among sampling sites that were 2–4 km apart. River pH showed a significant non‐linear relationship with normalised reads, with a peak in partial effect on normalised reads at pH 6.5. Partial effect on normalised reads also showed a positive linear relationship with flow (discharge), while also peaking at the highest average monthly air temperatures (14°C). These trends are contrary to what would be expected from eDNA decay, dilution or transport, demonstrating that metabarcoding is robust to such influences, reinforcing the interpretation of trends driven by Atlantic salmon ecology and physiology. For example, pH effects reflect beneficial conditions for eggs and perhaps habitat preference for spawners, flow effects reflect the annual return of salmon during higher flows which aid upstream migration, tributary entry and spawning, and, finally, temperature effects reflect higher metabolic rates and greater shedding of eDNA.

Uncovering the lazybones of the shark world - William Bernard Perry (Journal of Fish Biology, 2025)

A novel approach for quantifying elongated airborne mineral particles (EMPs) using an automated scanning electron microscope (SEM) - Anushka Elangasinghe; Hamesh Patel; Kim N. Dirks; Ayrton Hamilton; Wenxia (Wendy) Fan; Shuoyu Chen; Nick Talbot; Shanon Lim; Jed Januch; Martin Brook; Brett Wells; David E. Williams; et al. (Atmospheric Environment, 2025)

School's out, but not for fish that want to pass - William Bernard Perry (Journal of Fish Biology, 2025)

The Cost of Antivenom: A Cost Minimization Study using the North American Snakebite Registry - Benjamin Herzel; Neev Batavia; Paul Gavaza; Tammy Phan; Emmelyn Samones; Anne-Michelle Ruha; Jakub Furmaga; Christopher Hoyte; Brian J. Wolk; Peter Akpunonu; Adam Algren; Alexandra Amaducci; et al. (Journal of Medical Toxicology, 2025)
Envenomation is a global health issue, with over 9,000 encounters managed in the United States yearly. The introduction of immunoglobulin fragment antivenom has reduced the risk of hypersensitivity. This study compares treatment costs of crotaline envenomation using the Fab and F(ab’) 2 antivenoms as reported to the North American Snakebite Registry (NASBR), a nationwide surveillance tool. Methods This was a retrospective analysis of NASBR data between 2018 and 2020. The following data points were assessed: patient demographics (age, gender, race), snake species, type of antivenom used, and treatment costs. Unit costs were estimated based on United States Centers for Medicare and Medicaid Services data. Average (mean) per patient costs from the payer perspective were calculated by multiplying resources by the unit costs. Sensitivity analyses were performed regarding cost variance and snake species. All costs reported in this study are in U.S. dollars. Results The average total cost of treatment was $31,343 per person, with medications contributing 72% of the total. Average total cost among patients who received Fab treatments was $33,347 per person compared to $19,747 among patients who received F(ab’) 2 . Antivenom costs accounted for 75% of the total cost in the Fab group and 42% in the F(ab’) 2 group. F(ab’) 2 required more vials than Fab (median 18 versus 10). Non-antivenom costs such as hospitalizations were higher in the F(ab’) 2 group. Using average sale prices increased average total cost to $52,572; Fab remained more expensive. Conclusion Antivenom is the primary cost driver in snakebite treatment in North America. Treatment with F(ab’) 2 resulted in lower overall costs, driven by lower cost of antivenom. F(ab’) 2 did not significantly lower overall resource use except for blood product administration.

Put it in reverse! Captivating deep‐sea footage reveals the mysterious movements of abyssal fish - William Bernard Perry (Journal of Fish Biology, 2025)

Tough mothers and tender fathers: New assays reveal the behavioural complexity of the common clownfish - William Bernard Perry (Journal of Fish Biology, 2025)

Systemic toxicity after rattlesnake envenomation in patients using angiotensin converting enzyme inhibitors: A North American Snakebite Registry study - A.M. Ruha; M.B. Spyres; R. Culbreth; B. Wolk; C. Hoyte; S. Campleman; Peter Akpunonu; Adam Algren; Alexandra Amaducci; Sukhshant Atti; Connie Aubin; Kevin Baumgartner; et al. (Toxicon, 2025)

The grime fighting potential of fish guts and the battle for responsible consumption - William Bernard Perry (Journal of Fish Biology, 2025)

Lump by name, but not by nature: 1000km migration of lumpfish ( Cyclopterus lumpus ) - William Bernard Perry (Journal of Fish Biology, 2025)

Estimating Spatially Explicit Survival and Mortality Risk From Telemetry Data With Thinned Point Process Models - Joseph M. Eisaguirre; Madeleine G. Lohman; Graham G. Frye; Heather E. Johnson; Thomas V. Riecke; Perry J. Williams (Ecology Letters, 2025)
Mortality risk for animals often varies spatially and can be linked to how animals use landscapes. While numerous studies collect telemetry data on animals, the focus is typically on the period when animals are alive, even though there is important information that could be gleaned about mortality risk. We introduce a thinned spatial point process (SPP) modelling framework that couples relative abundance and space use with a mortality process to formally treat the occurrence of mortality events across the landscape as a spatial process. We show how this model can be embedded in a hierarchical statistical framework and fit to telemetry data to make inferences about how spatial covariates drive both space use and mortality risk. We apply the method to two data sets to study the effects of roads and habitat on spatially explicit mortality risk: (1) VHF telemetry data collected for willow ptarmigan in Alaska, and (2) hourly GPS telemetry data collected for black bears in Colorado. These case studies demonstrate the applicability of this method for different species and data types, making it broadly useful in enabling inferences about the mechanisms influencing animal survival and spatial population processes while formally treating survival as a spatial process, especially as the development and implementation of joint analyses continue to progress.

Pick on someone your own size! Arctic grayling ( Thymallus arcticus ), do. - William Bernard Perry (Journal of Fish Biology, 2025)

Metagenomics unveils the role of hospitals and wastewater treatment plants on the environmental burden of antibiotic resistance genes and opportunistic pathogens - Reshma Silvester; William B. Perry; Gordon Webster; Laura Rushton; Amy Baldwin; Daniel A. Pass; Nathaniel Healey; Kata Farkas; Noel Craine; Gareth Cross; Peter Kille; Andrew J. Weightman; et al. (Science of The Total Environment, 2025)

Aquatic habitat destruction in the Amazon and the unexpected response of fish - William Bernard Perry (Journal of Fish Biology, 2024)

Evaluating the efficacy of targeted traffic management interventions: A novel methodology for determining the composition of particulate matter in urban air pollution hotspots - Hamesh Patel; Perry Davy; Cherie Tollemache; Nick Talbot; Jennifer Salmond; David E. Williams (Science of The Total Environment, 2024)

Everybody needs good neighbours, even if you’re a winter flounder - William Bernard Perry (Journal of Fish Biology, 2024)

National-scale antimicrobial resistance surveillance in wastewater: A comparative analysis of HT qPCR and metagenomic approaches - Margaret E. Knight; Gordon Webster; William B. Perry; Amy Baldwin; Laura Rushton; Daniel A. Pass; Gareth Cross; Isabelle Durance; Windi Muziasari; Peter Kille; Kata Farkas; Andrew J. Weightman; et al. (Water Research, 2024)

Research and the environment, casualties of war - William Bernard Perry (Journal of Fish Biology, 2024)

Examining the stability of viral RNA and DNA in wastewater: Effects of storage time, temperature, and freeze-thaw cycles - Rachel C. Williams; William B. Perry; Kathryn Lambert-Slosarska; Ben Futcher; Cameron Pellett; India Richardson-O'Neill; Steve Paterson; Jasmine M.S. Grimsley; Matthew J. Wade; Andrew J. Weightman; Kata Farkas; Davey L. Jones (Water Research, 2024)

Sustainable mining in tropical, biodiverse landscapes: Environmental challenges and opportunities in the archipelagic Philippines - Justine Perry T. Domingo; Gawen R.T. Jenkin; Laura Quick; Richard D. Williams; Karen A. Hudson-Edwards; Cecilia Tortajada; Patrick Byrne; Tom J. Coulthard; Jenielyn T. Padrones; Rich Crane; Cris Reven L. Gibaga; Grigorios Vasilopoulos; et al. (Journal of Cleaner Production, 2024)

Identifying priority sites for whale shark ship collision management globally - Freya C. Womersley; Christoph A. Rohner; Kátya Abrantes; Pedro Afonso; Shin Arunrugstichai; Steffen S. Bach; Shir Bar; Adi Barash; Peter Barnes; Adam Barnett; Ginevra Boldrocchi; Noemie Buffat; et al. (Science of The Total Environment, 2024)

Going with the flow, especially if you are riddled with parasites - William Bernard Perry (Journal of Fish Biology, 2024)

James and the giant perch: a fresh framework for understanding gigantism in fish - William Bernard Perry (Journal of Fish Biology, 2024)

Sounds like a damsel in distress! - William Bernard Perry (Journal of Fish Biology, 2024)

Cross-continental comparative experiences of wastewater surveillance and a vision for the 21st century - William Bernard Perry; Mariana Cardoso Chrispim; Mikaela Renata Funada Barbosa; Marcelo de Souza Lauretto; Maria Tereza Pepe Razzolini; Adelaide Cassia Nardocci; Owen Jones; Davey L. Jones; Andrew Weightman; Maria Inês Zanoli Sato; Cassiana Montagner; Isabelle Durance (Science of The Total Environment, 2024)

Macabre ‘Finding Nemo’ remake, starring the reticulated damselfish ( Dascyllus reticulatus ) - William Bernard Perry (Journal of Fish Biology, 2024)

They grow up so fast, especially when global warming is concerned. - William Bernard Perry (Journal of Fish Biology, 2024)

Addressing the challenges of combined sewer overflows - William Bernard Perry; Reza Ahmadian; Max Munday; Owen Jones; Steve J. Ormerod; Isabelle Durance (Environmental Pollution, 2024)

Climbing the social ladder rewarded with sex change in Gorgeous gobies ( Lythrypnus pulchellus ) - William Bernard Perry (Journal of Fish Biology, 2024)

Limited summer palate with no colonic irrigation required: life of a migratory shark through the metabarcoding lens - William Bernard Perry (Journal of Fish Biology, 2023)

The ups and downs of Atlantic halibut spawning - William Bernard Perry (Journal of Fish Biology, 2023)

The environmental impact of keeping a tropical aquarium in Northern Europe - William Bernard Perry (Journal of Fish Biology, 2023)
Tropical fishkeeping is a popular practice in societies across the globe and involves recreating and sustaining an entire ecosystem in an aquarium within a domestic setting. The process invariably has an environmental impact, yet an assessment of this impact has previously been limited to the ecological consequences of harvesting fish from the wild or the release of non‐native fish species. Provided here are the first estimates of carbon dioxide equivalent (CO 2 eq) emissions produced from running a tropical aquarium across multiple countries in Northern Europe (France, Poland and the UK), along with water consumption. Estimates were produced in silico and are discussed in the context of freshwater and marine aquariums, calculated using example aquarium sizes of 50, 200 and 400 l. Using estimates from the UK, depending on size and running conditions, a tropical aquarium produces an estimated 85.3–635.2 kg of CO 2 eq per year, equating to 1.6%–12.4% of the UK annual average household CO 2 emissions, and uses 156–31,200 l of water per year, equating to 0.2%–30.1% of the UK annual average household water usage. Despite this, comparison with the CO 2 eq of an average‐size dog (127–1592 kg of CO 2 eq per year) or cat (121–251 kg of CO 2 eq per year), estimated from meat consumption alone, demonstrates that ornamental fishkeeping can be a more environmentally conscious pet choice. In addition, the majority of CO 2 eq produced from tropical fishkeeping is generated from the energy consumption of aquarium equipment and as more national electricity grids begin to decarbonize, this estimate should decrease.

The cold sting of climate change and its effect on the march of invasive fishes - William Bernard Perry (Journal of Fish Biology, 2023)

Even model organisms stress about moving house - William Bernard Perry (Journal of Fish Biology, 2023)

Mystery egg revealing secrets from the deep - William Bernard Perry (Journal of Fish Biology, 2023)

Dining amidst the decibels is not an issue when you have company: anthropogenic noise and the topmouth Gudgeon - William Bernard Perry (Journal of Fish Biology, 2023)

Turn left at the next rocky atoll: small fish fare well with new satellite tags - William Bernard Perry (Journal of Fish Biology, 2023)

A knight in shining armour: iridescence in male jewelled splitfin ( Xenotoca variata ) - William Bernard Perry (Journal of Fish Biology, 2023)

Travelling in the omics time machine: uncovering mysteries of the extinct Moroccan trout ( Salmo pallaryi ) - William Bernard Perry (Journal of Fish Biology, 2023)

Nutrient function over form: Organic and inorganic nitrogen additions have similar effects on lake phytoplankton nutrient limitation - Sabrina N. Volponi; Heather L. Wander; David C. Richardson; Clayton J. Williams; Denise A. Bruesewitz; Shelley Arnott; Jennifer A. Brentrup; Hailee L. Edwards; Holly A. Ewing; Kristen Holeck; Lauren Johnson; Brian S. Kim; et al. (Limnology and Oceanography, 2023)
The concentration of dissolved organic nitrogen (DON) is increasing in many northern hemisphere lakes, yet its use by phytoplankton and fate in the environment seldom have been quantified. We conducted 1 week, in situ, microcosm incubations across 25 lakes in northeastern North America to understand how DON, dissolved inorganic nitrogen (DIN), and dissolved inorganic phosphorus (P) affected phytoplankton biomass. In addition, we tested whether lakes were limited by single macronutrients (N or P) or colimited by both. Phytoplankton biomass in 80% of lakes responded similarly to DON and DIN additions. Of the lakes where N form produced differential responses, the majority of phytoplankton communities exhibited greater biomass accumulation with DON than DIN. Colimitation was the most common type of nutrient limitation among the study lakes, followed by P limitation. Limitation type shifted with N form in 40% of the study lakes, but without consistent patterns explaining how shifts occurred. Regardless of N form, lakes with watersheds more dominated by agriculture and higher total dissolved nitrogen (TDN) tended to show P‐limited phytoplankton responses, while lakes with less agricultural watersheds and lower TDN tended to show colimited phytoplankton responses. Finally, ambient TDN and total phosphorus (TP) nutrient concentrations were stronger predictors of limitation type than ambient TDN : TP ratios. The different contributions of DON and DIN to phytoplankton biomass in some of our study lakes suggest that DON loading from surrounding watersheds may be an overlooked component in predicting phytoplankton productivity and nutrient limitation dynamics in freshwater ecosystems.

The power of bringing science to the people - William Bernard Perry (Journal of Fish Biology, 2023)

Lymphomatosis as a Cause of Abdominal Pain and Distension in Two Adult Horses - Laura R. Perry; Amanda J. Butler; Emily John; Shannon Martinson; Melanie Buote; Kimberley Foote; Shelley Burton; William B. Stoughton (Journal of Equine Veterinary Science, 2023)

All roads lead to… fish egg and larvae literature? - William Bernard Perry (Journal of Fish Biology, 2023)

Sleeping with the fishes: Looking under the bonnet of melatonin synthesis - William Bernard Perry (Journal of Fish Biology, 2022)

Sex or snack? Drivers behind the behavioural mystery of basking shark circles revealed - William Bernard Perry (Journal of Fish Biology, 2022)

Bringing down the hammer on bycatch - William Bernard Perry (Journal of Fish Biology, 2022)

Emptying the file drawer: the importance of publishing non‐significance results in research - William Bernard Perry (Journal of Fish Biology, 2022)

Memantine treatment does not affect compulsive behavior or frontostriatal connectivity in an adolescent rat model for quinpirole-induced compulsive checking behavior - Milou Straathof; Erwin L. A. Blezer; Christel E. Smeele; Caroline van Heijningen; Annette van der Toorn; Jan K. Buitelaar; Jeffrey C. Glennon; Willem M. Otte; Rick M. Dijkhuizen; Jan Buitelaar; Saskia de Ruiter; Jilly Naaijen; et al. (Psychopharmacology, 2022)
Rationale Compulsivity often develops during childhood and is associated with elevated glutamate levels within the frontostriatal system. This suggests that anti-glutamatergic drugs, like memantine, may be an effective treatment. Objective Our goal was to characterize the acute and chronic effect of memantine treatment on compulsive behavior and frontostriatal network structure and function in an adolescent rat model of compulsivity. Methods Juvenile Sprague–Dawley rats received repeated quinpirole, resulting in compulsive checking behavior ( n = 32; compulsive) or saline injections ( n = 32; control). Eight compulsive and control rats received chronic memantine treatment, and eight compulsive and control rats received saline treatment for seven consecutive days between the 10th and 12th quinpirole/saline injection. Compulsive checking behavior was assessed, and structural and functional brain connectivity was measured with diffusion MRI and resting-state fMRI before and after treatment. The other rats received an acute single memantine (compulsive: n = 12; control: n = 12) or saline injection (compulsive: n = 4; control: n = 4) during pharmacological MRI after the 12th quinpirole/saline injection. An additional group of rats received a single memantine injection after a single quinpirole injection ( n = 8). Results Memantine treatment did not affect compulsive checking nor frontostriatal structural and functional connectivity in the quinpirole-induced adolescent rat model. While memantine activated the frontal cortex in control rats, no significant activation responses were measured after single or repeated quinpirole injections. Conclusions The lack of a memantine treatment effect in quinpirole-induced compulsive adolescent rats may be partly explained by the interaction between glutamatergic and dopaminergic receptors in the brain, which can be evaluated with functional MRI.

Is having more neural tissue really a no‐brainer? - William Bernard Perry (Journal of Fish Biology, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Better fisheries management? We're all (inner) ears! - William Bernard Perry (Journal of Fish Biology, 2022)

The bitterling's hunt for a cozy abode and the impact of freshwater habitat degradation - William Bernard Perry (Journal of Fish Biology, 2022)

Where the mysid shrimp go, dragons follow - William Bernard Perry (Journal of Fish Biology, 2022)

The Effect of Marsh Age on Ecosystem Function in a Rapidly Transgressing Marsh - Amy K. Langston; Daniel J. Coleman; Nathalie W. Jung; Justin L. Shawler; Alexander J. Smith; Bethany L. Williams; Serina S. Wittyngham; Randolph M. Chambers; James E. Perry; Matthew L. Kirwan (Ecosystems, 2022)

Holding it in: yet another consequence of our fragmented rivers - William Bernard Perry (Journal of Fish Biology, 2022)

Into the lion’s den: spawning success of lionfish ( Pterois miles) in the Mediterranean Sea - William Bernard Perry (Journal of Fish Biology, 2022)

The importance of 1.5°C warming for the Great Barrier Reef - Jennifer K. McWhorter; Paul R. Halloran; George Roff; William J. Skirving; Chris T. Perry; Peter J. Mumby (Global Change Biology, 2022)
Tropical coral reefs are among the most sensitive ecosystems to climate change and will benefit from the more ambitious aims of the United Nations Framework Convention on Climate Change's Paris Agreement, which proposed to limit global warming to 1.5° rather than 2°C above pre‐industrial levels. Only in the latest Intergovernmental Panel on Climate Change focussed assessment, the Coupled Model Intercomparison Project phase 6 (CMIP6), have climate models been used to investigate the 1.5° warming scenario directly. Here, we combine the most recent model updates from CMIP6 with a semi‐dynamic downscaling to evaluate the difference between the 1.5 and 2°C global warming targets on coral thermal stress metrics for the Great Barrier Reef (GBR). By ~2080, severe bleaching events are expected to occur annually under intensifying emissions (shared socioeconomic pathway SSP5‐8.5). Adherence to 2° warming (SSP1‐2.6) halves this frequency but the main benefit of confining warming to 1.5° (SSP1‐1.9) is that bleaching events are reduced further to 3 events per decade. Attaining low emissions of 1.5° is also paramount to prevent the mean magnitude of thermal stress from stabilizing close to a critical thermal threshold (8 Degree Heating Weeks). Thermal stress under the more pessimistic pathways SSP3‐7.0 and SSP5‐8.5 is three to fourfold higher than the present day, with grave implications for future reef ecosystem health. As global warming continues, our projections also indicate more regional warming in the central and southern GBR than the far north and northern GBR.

Recursive Bayesian computation facilitates adaptive optimal design in ecological studies - Clinton B. Leach; Perry J. Williams; Joseph M. Eisaguirre; Jamie N. Womble; Michael R. Bower; Mevin B. Hooten (Ecology, 2022)
Optimal design procedures provide a framework to leverage the learning generated by ecological models to flexibly and efficiently deploy future monitoring efforts. At the same time, Bayesian hierarchical models have become widespread in ecology and offer a rich set of tools for ecological learning and inference. However, coupling these methods with an optimal design framework can become computationally intractable. Recursive Bayesian computation offers a way to substantially reduce this computational burden, making optimal design accessible for modern Bayesian ecological models. We demonstrate the application of so‐called prior‐proposal recursive Bayes to optimal design using a simulated data binary regression and the real‐world example of monitoring and modeling sea otters in Glacier Bay, Alaska. These examples highlight the computational gains offered by recursive Bayesian methods and the tighter fusion of monitoring and science that those computational gains enable.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

The devastating duo: bycatch and climate change hit the Atlantic wolffish Anarhichas lupus - William Bernard Perry (Journal of Fish Biology, 2022)

Turbo charged salmon and stream ecosystem function: the plight of aquaculture escapees - William Bernard Perry (Journal of Fish Biology, 2021)

Escaping the fate of Sisyphus: assessing resistome hybridization baits for antimicrobial resistance gene capture - Megan S. Beaudry; Jesse C. Thomas; Rodrigo P. Baptista; Amanda H. Sullivan; William Norfolk; Alison Devault; Jacob Enk; Troy J. Kieran; Olin E. Rhodes; K. Allison Perry‐Dow; Laura J. Rose; Natalia J. Bayona‐Vásquez; et al. (Environmental Microbiology, 2021)
Summary Finding, characterizing and monitoring reservoirs for antimicrobial resistance (AMR) is vital to protecting public health. Hybridization capture baits are an accurate, sensitive and cost‐effective technique used to enrich and characterize DNA sequences of interest, including antimicrobial resistance genes (ARGs), in complex environmental samples. We demonstrate the continued utility of a set of 19 933 hybridization capture baits designed from the Comprehensive Antibiotic Resistance Database (CARD)v1.1.2 and Pathogenicity Island Database (PAIDB)v2.0, targeting 3565 unique nucleotide sequences that confer resistance. We demonstrate the efficiency of our bait set on a custom‐made resistance mock community and complex environmental samples to increase the proportion of on‐target reads as much as >200‐fold. However, keeping pace with newly discovered ARGs poses a challenge when studying AMR, because novel ARGs are continually being identified and would not be included in bait sets designed prior to discovery. We provide imperative information on how our bait set performs against CARDv3.3.1, as well as a generalizable approach for deciding when and how to update hybridization capture bait sets. This research encapsulates the full life cycle of baits for hybridization capture of the resistome from design and validation (both in silico and in vitro ) to utilization and forecasting updates and retirement.

Sex, smells and sickness: deceitful mate choice in Nile tilapia - William Bernard Perry (Journal of Fish Biology, 2021)

Complexity is key: fish diversity and tropical inshore seascapes - William Bernard Perry (Journal of Fish Biology, 2021)

Life in captivity: future research in physical enrichment for fish - William Bernard Perry (Journal of Fish Biology, 2021)

When it comes to brown trout and arctic charr migrants, home is where the heart is - William Bernard Perry (Journal of Fish Biology, 2021)

Some rays get extra help from their mothers - William Bernard Perry (Journal of Fish Biology, 2021)

Recycling of Nitrate and Organic Matter by Plants in the Vadose Zone of a Saturated Riparian Buffer - Patience Bosompemaa; Eric Wade Peterson; William Perry; Wondwosen M. Seyoum (Water, Air, & Soil Pollution, 2021)

Spatiotemporal Analysis of Water Quality Indicators in Small Lakes Using Sentinel-2 Satellite Data: Lake Bloomington and Evergreen Lake, Central Illinois, USA - Gare Ambrose-Igho; Wondwosen M. Seyoum; William L. Perry; Catherine M. O’Reilly (Environmental Processes, 2021)

Corrigendum: OceanGliders: A Component of the Integrated GOOS - Pierre Testor; Brad de Young; Daniel L. Rudnick; Scott Glenn; Daniel Hayes; Craig M. Lee; Charitha Pattiaratchi; Katherine Hill; Emma Heslop; Victor Turpin; Pekka Alenius; Carlos Barrera; et al. (Frontiers in Marine Science, 2021)

Harbor Seals as Sentinels of Ice Dynamics in Tidewater Glacier Fjords - Jamie N. Womble; Perry J. Williams; Robert W. McNabb; Anupma Prakash; Rudiger Gens; Benjamin S. Sedinger; Cheyenne R. Acevedo (Frontiers in Marine Science, 2021)
Tidewater glaciers calve icebergs into the marine environment which serve as pupping, molting, and resting habitat for some of the largest seasonal aggregations of harbor seals ( Phoca vitulina richardii ) in the world. Although they are naturally dynamic, advancing and retreating in response to local climatic and fjord conditions, most tidewater glaciers around the world are thinning and retreating. Climate change models predict continued loss of land-based ice with unknown impacts to organisms such as harbor seals that rely on glacier ice as habitat for critical life history events. To understand the impacts of changing ice availability on harbor seals, we quantified seasonal and annual changes in ice habitat in Johns Hopkins Inlet, a tidewater glacier fjord in Glacier Bay National Park in southeastern Alaska. We conducted systematic aerial photographic surveys ( n = 55) of seals and ice during the pupping (June; n = 30) and molting (August; n = 25) periods from 2007 to 2014. Object-based image analysis was used to quantify the availability and spatial distribution of floating ice in the fjord. Multivariate spatial models were developed for jointly modeling stage-structured seal location data and ice habitat. Across all years, there was consistently more ice in the fjord during the pupping season in June than during the molting season in August, which was likely driven by seasonal variation in physical processes that influence the calving dynamics of tidewater glaciers. Non-pup harbor seals and ice were correlated during the pupping season, but this correlation was reduced during the molting season suggesting that harbor seals may respond to changes in habitat differently depending upon trade-offs associated with life history events, such as pupping and molting, and energetic costs and constraints associated with the events.

Foul play: the impact of dog waste on freshwater fish - William Bernard Perry (Journal of Fish Biology, 2021)

Characterisation of LV myocardial exercise function by 2-D strain deformation imaging in elite adolescent footballers - Guido E. Pieles; Lucy Gowing; Diane Ryding; Dave Perry; Steven R. McNally; A. Graham Stuart; Craig A. Williams (European Journal of Applied Physiology, 2021)
Purpose Few data exist on the descriptions of LV myocardial mechanics and reserve during dynamic exercise of adolescent athletes. The aim of this study was to describe the LV myocardial and cardiopulmonary changes during exercise using 2-D strain deformation imaging. Methods Elite adolescent male football players ( n = 42) completed simultaneous cardiopulmonary exercise testing (CPET) and exercise echocardiography measurement of LV myocardial deformation by 2-D strain imaging. LV longitudinal and circumferential 2-D strain and strain rates were analyzed at each stage during incremental exercise to a work rate of 150 W. Additionally, exercise LV myocardial deformation and its relation to metabolic exercise parameters were evaluated at each exercise stage and in recovery using repeated measures ANOVA, linear regression and paired t tests. Results LV peak systolic baseline 2-D strain (longitudinal: − 15.4 ± 2.5%, circumferential: − 22.5 ± 3.1%) increased with each exercise stage, but longitudinal strain plateaued at 50 W (mean strain reserve − 7.8 ± 3.0) and did not significantly increase compared to subsequent exercise stages ( P > 0.05), whilst circumferential strain (mean strain reserve − 11.6 ± 3.3) significantly increased ( P < 0.05) throughout exercise up to 150 W as the dominant mechanism of exercise LV contractility increase. Regression analyses showed LV myocardial strain increased linearly relative to HR, VO 2 and O 2 pulse ( P < 0.05) for circumferential deformation, but showed attenuation for longitudinal deformation. Conclusion This study describes LV myocardial deformation dynamics by 2-D strain and provides reference values for LV myocardial strain and strain rate during exercise in adolescent footballers. It found important differences between LV longitudinal and circumferential myocardial mechanics during exercise and introduces a methodology that can be used to quantify LV function and cardiac reserve during exercise in adolescent athletes.

Considerations for Offshore Wind Energy Development Effects on Fish and Fisheries in the United States: A Review of Existing Studies, New Efforts, and Opportunities for Innovation - Ruth Perry; William Heyman (Oceanography, 2020)

A review of a decade of lessons from one of the world’s largest MPAs: conservation gains and key challenges - Graeme C. Hays; Heather J. Koldewey; Samantha Andrzejaczek; Martin J. Attrill; Shanta Barley; Daniel T. I. Bayley; Cassandra E. Benkwitt; Barbara Block; Robert J. Schallert; Aaron B. Carlisle; Pete Carr; Taylor K. Chapple; et al. (Marine Biology, 2020)

Steps to Develop Early Warning Systems and Future Scenarios of Storm Wave-Driven Flooding Along Coral Reef-Lined Coasts - Gundula Winter; Curt Storlazzi; Sean Vitousek; Ap van Dongeren; Robert McCall; Ron Hoeke; William Skirving; John Marra; Johan Reyns; Jerome Aucan; Matthew Widlansky; Janet Becker; et al. (Frontiers in Marine Science, 2020)

Temporal population variability in local forest communities has mixed effects on tree species richness across a latitudinal gradient - Tak Fung; Ryan A. Chisholm; Kristina Anderson‐Teixeira; Norm Bourg; Warren Y. Brockelman; Sarayudh Bunyavejchewin; Chia‐Hao Chang‐Yang; Rutuja Chitra‐Tarak; George Chuyong; Richard Condit; Handanakere S. Dattaraja; Stuart J. Davies; et al. (Ecology Letters, 2020)
Among the local processes that determine species diversity in ecological communities, fluctuation‐dependent mechanisms that are mediated by temporal variability in the abundances of species populations have received significant attention. Higher temporal variability in the abundances of species populations can increase the strength of temporal niche partitioning but can also increase the risk of species extinctions, such that the net effect on species coexistence is not clear. We quantified this temporal population variability for tree species in 21 large forest plots and found much greater variability for higher latitude plots with fewer tree species. A fitted mechanistic model showed that among the forest plots, the net effect of temporal population variability on tree species coexistence was usually negative, but sometimes positive or negligible. Therefore, our results suggest that temporal variability in the abundances of species populations has no clear negative or positive contribution to the latitudinal gradient in tree species richness.

OceanGliders: A Component of the Integrated GOOS - Pierre Testor; Brad de Young; Daniel L. Rudnick; Scott Glenn; Daniel Hayes; Craig M. Lee; Charitha Pattiaratchi; Katherine Hill; Emma Heslop; Victor Turpin; Pekka Alenius; Carlos Barrera; et al. (Frontiers in Marine Science, 2019)
The OceanGliders program started in 2016 to support active coordination and enhancement of global glider activity. OceanGliders contributes to the international efforts of the Global Ocean Observation System (GOOS) for Climate, Ocean Health, and Operational Services. It brings together marine scientists and engineers operating gliders around the world: (1) to observe the long-term physical, biogeochemical, and biological ocean processes and phenomena that are relevant for societal applications; and, (2) to contribute to the GOOS through real-time and delayed mode data dissemination. The OceanGliders program is distributed across national and regional observing systems and significantly contributes to integrated, multi-scale and multi-platform sampling strategies. OceanGliders shares best practices, requirements, and scientific knowledge needed for glider operations, data collection and analysis. It also monitors global glider activity and supports the dissemination of glider data through regional and global databases, in real-time and delayed modes, facilitating data access to the wider community. OceanGliders currently supports national, regional and global initiatives to maintain and expand the capabilities and application of gliders to meet key global challenges such as improved measurement of ocean boundary currents, water transformation and storm forecast.

The Second Warning to Humanity – Providing a Context for Wetland Management and Policy - C. M. Finlayson; Gillian T. Davies; William R. Moomaw; G. L. Chmura; Susan M. Natali; J. E. Perry; N. Roulet; Ariana E. Sutton-Grier (Wetlands, 2019)

Evaluation of a traditional Māori harvesting method for sampling kōura (freshwater crayfish, Paranephrops planifrons ) and toi toi (bully, Gobiomorphus spp.) populations in two New Zealand streams - Ian A. Kusabs; Brendan J. Hicks; John M. Quinn; William L. Perry; Hēmi Whaanga (New Zealand Journal of Marine and Freshwater Research, 2018)
Representative sampling of crayfish in streams is often impractical, especially in non‐wadable habitats, or in areas with soft substrates. Whakaweku are artificial habitats made from bracken fern ( Pteridium esculentum ) that can be used successfully in a range of habitats. We compared whakaweku, minnow traps, fyke nets and electrofishing for sampling freshwater crayfish (kōura; Paranephrops planifrons ) and bullies (toi toi; Gobiomorphus spp .) in two streams with differing stream characteristics and fish assemblages. Whakaweku captured a full‐size range of kōura of both sexes, including small kōura (OCL 7–12 mm) that were not caught by minnow traps or fyke nets. Colonisation by kōura reached 90% of maximum after 2 weeks and CPUE was constant from 2 to 9 weeks. After 9 weeks, CPUE decreased due to decay of the fern fronds. Whakaweku are an effective sampling tool that are inexpensive, simple to set, and do not require expensive equipment or specialised training.

Chemotaxonomy of kōwhai: leaf and seed flavonoids of New Zealand Sophora species - Owen Michael McDougal; Peter Brian Heenan; Nigel Brian Perry; John William van Klink (New Zealand Journal of Botany, 2018)
Chemotaxonomic analysis of kōwhai leaf extracts in New Zealand are limited with previous reports of Sophora tetraptera having a flavonoid profile distinct from S. microphylla sensu lato and S. prostrata . Eight Sophora species are now recognised in New Zealand: S. chathamica , S. fulvida , S. godleyi , S. longicarinata , S. microphylla , S. molloyi , S. prostrata and S. tetraptera . We now report liquid chromatography‐ultraviolet‐mass spectrometry (LC‐UV‐MS) analyses of leaf and seed extracts of individual plants (2–16) from each of these eight species, plus the Chilean S. cassioides . All of the S. tetraptera leaf extracts had similar LC‐UV‐MS profiles, different from all of the other Sophora samples, consisting of four predominant compounds, characterised by MS and nuclear magnetic resonance (NMR) spectroscopy as: luteolin‐7‐O‐rutinoside 1 , luteolin‐7‐O‐glucoside 2 , apigenin‐7‐O‐rutinoside 3 , and apigenin‐7‐O‐glucoside 4 . The other Sophora leaf extracts showed complex flavonoid compositions, with no clear distinction between species. Most of the Sophora seed samples, including those of S. tetraptera , showed one major phenolic compound, but a few had a related compound. These were purified and characterised by MS and NMR spectroscopy as 3′,4′,7‐trihydroxyisoflavone 5 (in most seeds) and its 7‐O‐glucoside 6 (in a few seeds), neither of which has been previously reported from these Sophora species.

Front Cover - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)

Global importance of large‐diameter trees - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)
Aim To examine the contribution of large‐diameter trees to biomass, stand structure, and species richness across forest biomes. Location Global. Time period Early 21st century. Major taxa studied Woody plants. Methods We examined the contribution of large trees to forest density, richness and biomass using a global network of 48 large (from 2 to 60 ha) forest plots representing 5,601,473 stems across 9,298 species and 210 plant families. This contribution was assessed using three metrics: the largest 1% of trees ≥ 1 cm diameter at breast height (DBH), all trees ≥ 60 cm DBH, and those rank‐ordered largest trees that cumulatively comprise 50% of forest biomass. Results Averaged across these 48 forest plots, the largest 1% of trees ≥ 1 cm DBH comprised 50% of aboveground live biomass, with hectare‐scale standard deviation of 26%. Trees ≥ 60 cm DBH comprised 41% of aboveground live tree biomass. The size of the largest trees correlated with total forest biomass ( r 2 = .62, p r 2 = .45, p r 2 = .33, p r 2 = .17, p = .002). The concentration of biomass in the largest 1% of trees declined with increasing absolute latitude ( r 2 = .46, p r 2 = .31, p r 2 = .26, p Main conclusions Because large‐diameter trees constitute roughly half of the mature forest biomass worldwide, their dynamics and sensitivities to environmental change represent potentially large controls on global forest carbon cycling. We recommend managing forests for conservation of existing large‐diameter trees or those that can soon reach large diameters as a simple way to conserve and potentially enhance ecosystem services.

Wetlands In a Changing Climate: Science, Policy and Management - William R. Moomaw; G. L. Chmura; Gillian T. Davies; C. M. Finlayson; B. A. Middleton; Susan M. Natali; J. E. Perry; N. Roulet; Ariana E. Sutton-Grier (Wetlands, 2018)

Monitoring dynamic spatio‐temporal ecological processes optimally - Perry J. Williams; Mevin B. Hooten; Jamie N. Womble; George G. Esslinger; Michael R. Bower (Ecology, 2018)
Population dynamics vary in space and time. Survey designs that ignore these dynamics may be inefficient and fail to capture essential spatio‐temporal variability of a process. Alternatively, dynamic survey designs explicitly incorporate knowledge of ecological processes, the associated uncertainty in those processes, and can be optimized with respect to monitoring objectives. We describe a cohesive framework for monitoring a spreading population that explicitly links animal movement models with survey design and monitoring objectives. We apply the framework to develop an optimal survey design for sea otters in Glacier Bay. Sea otters were first detected in Glacier Bay in 1988 and have since increased in both abundance and distribution; abundance estimates increased from 5 otters to >5,000 otters, and they have spread faster than 2.7 km/yr. By explicitly linking animal movement models and survey design, we are able to reduce uncertainty associated with forecasting occupancy, abundance, and distribution compared to other potential random designs. The framework we describe is general, and we outline steps to applying it to novel systems and taxa.

Mother–infant interactions and regional brain volumes in infancy: an MRI study - Vaheshta Sethna; Inês Pote; Siying Wang; Maria Gudbrandsen; Anna Blasi; Caroline McCusker; Eileen Daly; Emily Perry; Kerrie P. H. Adams; Maria Kuklisova-Murgasova; Paula Busuulwa; Sarah Lloyd-Fox; et al. (Brain Structure and Function, 2017)

The basis function approach for modeling autocorrelation in ecological data - Trevor J. Hefley; Kristin M. Broms; Brian M. Brost; Frances E. Buderman; Shannon L. Kay; Henry R. Scharf; John R. Tipton; Perry J. Williams; Mevin B. Hooten (Ecology, 2017)
Analyzing ecological data often requires modeling the autocorrelation created by spatial and temporal processes. Many seemingly disparate statistical methods used to account for autocorrelation can be expressed as regression models that include basis functions. Basis functions also enable ecologists to modify a wide range of existing ecological models in order to account for autocorrelation, which can improve inference and predictive accuracy. Furthermore, understanding the properties of basis functions is essential for evaluating the fit of spatial or time‐series models, detecting a hidden form of collinearity, and analyzing large data sets. We present important concepts and properties related to basis functions and illustrate several tools and techniques ecologists can use when modeling autocorrelation in ecological data.

An integrated data model to estimate spatiotemporal occupancy, abundance, and colonization dynamics - Perry J. Williams; Mevin B. Hooten; Jamie N. Womble; George G. Esslinger; Michael R. Bower; Trevor J. Hefley (Ecology, 2017)
Ecological invasions and colonizations occur dynamically through space and time. Estimating the distribution and abundance of colonizing species is critical for efficient management or conservation. We describe a statistical framework for simultaneously estimating spatiotemporal occupancy and abundance dynamics of a colonizing species. Our method accounts for several issues that are common when modeling spatiotemporal ecological data including multiple levels of detection probability, multiple data sources, and computational limitations that occur when making fine‐scale inference over a large spatiotemporal domain. We apply the model to estimate the colonization dynamics of sea otters ( Enhydra lutris ) in Glacier Bay, in southeastern Alaska.

Amphetamine increases activity but not exploration in humans and mice - Arpi Minassian; Jared W. Young; Zackary A. Cope; Brook L. Henry; Mark A. Geyer; William Perry (Psychopharmacology, 2016)

Confirmation of delayed canopy wilting QTLs from multiple soybean mapping populations - Sadal Hwang; C. Andy King; Jeffery D. Ray; Perry B. Cregan; Pengyin Chen; Thomas E. Carter; Zenglu Li; Hussein Abdel-Haleem; Kevin W. Matson; William Schapaugh; Larry C. Purcell (Theoretical and Applied Genetics, 2015)

CTFS ‐Forest GEO : a worldwide network monitoring forests in an era of global change - Kristina J. Anderson‐Teixeira; Stuart J. Davies; Amy C. Bennett; Erika B. Gonzalez‐Akre; Helene C. Muller‐Landau; S. Joseph Wright; Kamariah Abu Salim; Angélica M. Almeyda Zambrano; Alfonso Alonso; Jennifer L. Baltzer; Yves Basset; Norman A. Bourg; et al. (Global Change Biology, 2015)
Global change is impacting forests worldwide, threatening biodiversity and ecosystem services including climate regulation. Understanding how forests respond is critical to forest conservation and climate protection. This review describes an international network of 59 long‐term forest dynamics research sites ( CTFS ‐Forest GEO ) useful for characterizing forest responses to global change. Within very large plots (median size 25 ha), all stems ≥1 cm diameter are identified to species, mapped, and regularly recensused according to standardized protocols. CTFS ‐Forest GEO spans 25°S–61°N latitude, is generally representative of the range of bioclimatic, edaphic, and topographic conditions experienced by forests worldwide, and is the only forest monitoring network that applies a standardized protocol to each of the world's major forest biomes. Supplementary standardized measurements at subsets of the sites provide additional information on plants, animals, and ecosystem and environmental variables. CTFS ‐Forest GEO sites are experiencing multifaceted anthropogenic global change pressures including warming (average 0.61 °C), changes in precipitation (up to ±30% change), atmospheric deposition of nitrogen and sulfur compounds (up to 3.8 g N m −2 yr −1 and 3.1 g S m −2 yr −1 ), and forest fragmentation in the surrounding landscape (up to 88% reduced tree cover within 5 km). The broad suite of measurements made at CTFS ‐Forest GEO sites makes it possible to investigate the complex ways in which global change is impacting forest dynamics. Ongoing research across the CTFS ‐Forest GEO network is yielding insights into how and why the forests are changing, and continued monitoring will provide vital contributions to understanding worldwide forest diversity and dynamics in an era of global change.

Persistent neurocognitive decline in a clinic sample of hepatitis C virus-infected persons receiving interferon and ribavirin treatment - Jordan E. Cattie; Scott L. Letendre; Steven Paul Woods; Fatma Barakat; William Perry; Mariana Cherner; Anya Umlauf; Donald Franklin; Robert K. Heaton; Tarek Hassanein; Igor Grant (Journal of NeuroVirology, 2014)

Primates and Cameras - Brian D. Gerber; Perry J. Williams; Larissa L. Bailey (International Journal of Primatology, 2014)

Capsaicin induces apoptosis in human small cell lung cancer via the TRPV6 receptor and the calpain pathway - Jamie K. Lau; Kathleen C. Brown; Aaron M. Dom; Theodore R. Witte; Brent A. Thornhill; Clayton M. Crabtree; Haley E. Perry; J. Michael Brown; John G. Ball; Rebecca G. Creel; C. Luke Damron; William D. Rollyson; et al. (Apoptosis, 2014)

Importance of Biogeomorphic and Spatial Properties in Assessing a Tidal Salt Marsh Vulnerability to Sea-level Rise - Karen M. Thorne; Deborah L. Elliott-Fisk; Glenn D. Wylie; William M. Perry; John Y. Takekawa (Estuaries and Coasts, 2014)

The Influence of Freshwater on Nekton Community Structure in Hydrologically Distinct Basins in Northeastern Florida Bay, FL, USA - Kerry E. Flaherty; Richard E. Matheson; Robert H. McMichael; William B. Perry (Estuaries and Coasts, 2013)

Mechanisms underlying plant sexual dimorphism in multi‐trophic arthropod communities - William K. Petry; Kayla I. Perry; Aleshia Fremgen; Sarah K. Rudeen; Mitchell Lopez; John Dryburgh; Kailen A. Mooney (Ecology, 2013)
A growing body of research documents the importance of plant genetic effects on arthropod community structure. However, the mechanisms underlying these effects are often unclear. Additionally, plant genetic effects have largely been quantified in common gardens, thus inflating the estimates of their importance by minimizing levels of natural variation. Using Valeriana edulis , a dioecious plant with genetically based sex determination, we conducted surveys and experiments on wild‐grown individuals to document field patterns of arthropod association between the sexes and the mechanisms underlying these plant genetic effects. Three years of surveys revealed strong and consistent sex‐biased arthropod association in wild‐grown plants: female plants supported 4‐fold, 1.5‐fold, and 4‐fold higher densities of aphids, aphid predators, and aphid‐tending ants, respectively, compared to males. There was mixed evidence that the female bias for aphids was due to higher plant quality, while we found no difference between plant sexes in aphid preference or the top‐down effects of predators and tending ants. Female bias for ants was due to both the greater attractiveness of female plants (direct effect mediated by floral nectar) and an independent, weaker effect of higher aphid abundance on females (density‐mediated indirect effect). Conversely, the female bias for predators was driven solely by the greater attractiveness of female plants. We did not find interaction modification, i.e., ant–aphid and predator–aphid interactions were equivalent between plant sexes. Plant sex explained 0.24%, 2.28%, and 4.42% of the variance in aphids, predators, and ants, respectively, values comparable to but slightly weaker than those previously reported from common‐garden studies. In contrast to the prediction of diminished plant genetic effects with increasing trophic level, we show how weak indirect effects on predators and parasitoids (via herbivores) can be complemented by strong direct effects via common plant traits (floral resources). In summary, we document direct and indirect effects of genetically based sex on a multi‐trophic arthropod community that were expressed in wild‐grown plants across multiple years.

Effects of risperidone, amisulpride and nicotine on eye movement control and their modulation by schizotypy - Anne Schmechtig; Jane Lees; Lois Grayson; Kevin J. Craig; Rukiya Dadhiwala; Gerard R. Dawson; J. F. William Deakin; Colin T. Dourish; Ivan Koychev; Katrina McMullen; Ellen M. Migo; Charlotte Perry; et al. (Psychopharmacology, 2013)

The safety of studies with intravenous Δ9-tetrahydrocannabinol in humans, with case histories - Michelle Carbuto; R. Andrew Sewell; Ashley Williams; Kim Forselius-Bielen; Gabriel Braley; Jacqueline Elander; Brian Pittman; Ashley Schnakenberg; Savita Bhakta; Edward Perry; Mohini Ranganathan; Deepak Cyril D’Souza (Psychopharmacology, 2012)

Projected Reorganization of Florida Bay Seagrass Communities in Response to the Increased Freshwater Inflow of Everglades Restoration - Darrell Anthony Herbert; William B. Perry; Bernard J. Cosby; James W. Fourqurean (Estuaries and Coasts, 2011)

A Rosette for Sampling Ice-Covered Water - William Smethie; Dale Chayes; Richard Perry; Peter Schlosser; Ronny Friedrich (Oceanography, 2011)

Effect of methamphetamine dependence on inhibitory deficits in a novel human open-field paradigm - Brook L. Henry; Arpi Minassian; Mandy van Rhenen; Jared W. Young; Mark A. Geyer; William Perry (Psychopharmacology, 2011)

Status and future of the forest health indicators program of the USA - Christopher William Woodall; Michael C. Amacher; William A. Bechtold; John W. Coulston; Sarah Jovan; Charles H. Perry; KaDonna C. Randolph; Beth K. Schulz; Gretchen C. Smith; Borys Tkacz; Susan Will-Wolf (Environmental Monitoring and Assessment, 2011)

Erratum to: Measuring sediment accretion in early tidal marsh restoration - John Y. Takekawa; Isa Woo; Nicole D. Athearn; Scott Demers; Rachel J. Gardiner; William M. Perry; Neil K. Ganju; Gregory G. Shellenbarger; David H. Schoellhamer (Wetlands Ecology and Management, 2010)

Measuring sediment accretion in early tidal marsh restoration - John Y. Takekawa; Isa Woo; Nicole D. Athearn; Scott Demers; Rachel J. Gardiner; William M. Perry; Neil K. Ganju; Gregory G. Shellenbarger; David H. Schoellhamer (Wetlands Ecology and Management, 2010)

Nicotine self-administration in the rat: effects of hypocretin antagonists and changes in hypocretin mRNA - Mark G. LeSage; Jennifer L. Perry; Catherine M. Kotz; David Shelley; William A. Corrigall (Psychopharmacology, 2010)

GBR 12909 administration as a mouse model of bipolar disorder mania: mimicking quantitative assessment of manic behavior - Jared W. Young; Andrew K. L. Goey; Arpi Minassian; William Perry; Martin P. Paulus; Mark A. Geyer (Psychopharmacology, 2010)

Observing Biogeochemical Cycles at Global Scales with Profiling Floats and Gliders: Prospects for a Global Array - Kenneth Johnson; William Berelson; Emmanuel Boss; Zanna Chase; Hervé Claustre; Steven Emerson; Nicolas Gruber; Arne Körtzinger; Mary Jane Perry; Stephen Riser (Oceanography, 2009)

Effects of 14 days of microgravity on fast hindlimb and diaphragm muscles of the rat - Mark D. Schuenke; David W. Reed; William J. Kraemer; Robert S. Staron; Jeff S. Volek; Wesley C. Hymer; Scott Gordon; L. Perry Koziris (European Journal of Applied Physiology, 2009)

Everglades restoration and water quality challenges in south Florida - William B. Perry (Ecotoxicology, 2008)

Federated Access to Heterogeneous Information Resources in the Neuroscience Information Framework (NIF) - Amarnath Gupta; William Bug; Luis Marenco; Xufei Qian; Christopher Condit; Arun Rangarajan; Hans Michael Müller; Perry L. Miller; Brian Sanders; Jeffrey S. Grethe; Vadim Astakhov; Gordon Shepherd; et al. (Neuroinformatics, 2008)

The Neuroscience Information Framework: A Data and Knowledge Environment for Neuroscience - Daniel Gardner; Huda Akil; Giorgio A. Ascoli; Douglas M. Bowden; William Bug; Duncan E. Donohue; David H. Goldberg; Bernice Grafstein; Jeffrey S. Grethe; Amarnath Gupta; Maryam Halavi; David N. Kennedy; et al. (Neuroinformatics, 2008)

Monoclonal antibodies reveal changes in predator efficiency with prey spatial pattern - GEORGIANNE J. K. GRIFFITHS; COLIN J. ALEXANDER; JOHN M. HOLLAND; PETER J. KENNEDY; JOE N. PERRY; WILLIAM O. C. SYMONDSON; LINTON WINDER (Molecular Ecology, 2008)
Spatially explicit predator–prey interactions can alter the predatory potential of natural enemies augmented through conservation biological control. To test hypotheses regarding such interactions and predatory efficiency, we used a combination of molecular techniques and mark–release–recapture to study the foraging behaviour of a generalist carabid predator, Poecilus cupreus , in response to spatial patterns of its cereal aphid prey ( Metapolophium dirhodum and Sitobion avenae ). Beetle and aphid numbers were measured across two grids of sampling locations, within which aphid spatial pattern had been manipulated to generate patchy and more homogenous distributions. Aphid consumption was measured by enzyme‐linked immunosorbent assays (ELISA) of beetle gut contents, using an aphid‐specific monoclonal antibody. Movement and distribution patterns suggest that P. cupreus does not aggregate at, nor instigate prey‐taxis within, aphid patches. However, more than two‐thirds of the 2169 P. cupreus tested by ELISA had consumed aphids and the proportion of beetles containing aphid proteins was positively related to aphid density. Against expectation, the proportion of predators feeding on aphids was greatest where prey were homogenously distributed, and this was attributed to the loss of partial refuges for prey in aphid patches. The functional value of this type of uniform foraging strategy is ideally suited to early colonization of the crop habitat, when aphid numbers are low, before populations build up and form strong spatial patterns.

Effects of graded levels of exercise on ipsilateral and contralateral post-exercise resting rectus femoris mechanomyography - William P. S. McKay; Perry Jacobson; Philip D. Chilibeck; Brian L. F. Daku (European Journal of Applied Physiology, 2006)

Disturbance frequency and community structure in a twenty-five year intervention study - Joel C. Trexler; William F. Loftus; Sue Perry (Oecologia, 2005)

Analysis of Historical Salinity and Boron Surface Water Monitoring Data from the San Joaquin River Watershed: 1985–2002 - Lenwood W. Hall; William D. Killen; Ronald D. Anderson; Elgin Perry (Environmental Monitoring and Assessment, 2004)

Elements of South Florida's Comprehensive Everglades Restoration Plan - William Perry (Ecotoxicology, 2004)

Ecological and economic implications of a tropical jellyfish invader in the Gulf of Mexico - William M. Graham; Daniel L. Martin; Darryl L. Felder; Vernon L. Asper; Harriet M. Perry (Biological Invasions, 2003)

Implications of Hybridization between Introduced and Resident Orconectes Crayfishes - William L. Perry; Jeffrey L. Feder; David M. Lodge (Conservation Biology, 2001)
One of the most imperiled taxonomic groups in North American freshwaters is that of crayfish ( Decapoda: Astacoidea): over 30% of the 390 species are threatened or endangered. This situation is globally significant because 80% of the world's crayfish species are North American. Few studies have examined the environmental changes that most threaten crayfish biodiversity, but competition and hybridization with non‐native crayfishes appear to be among the most important threats to native crayfishes. The rusty crayfish, Orconectes rusticus , native to southwestern Ohio has been introduced widely throughout the United States and is displacing two resident taxa, O. propinquus and O. virilis , in northern Wisconsin. Using morphological and allozyme comparisons of crayfish from allopatric and sympatric populations, we tested whether O. rusticus is hybridizing with the resident crayfishes in northern Wisconsin. We found no evidence of hybridization between O. virilis and either O. rusticus or O. propinquus . In contrast, numerous morphologically intermediate crayfish between O. rusticus and O. propinquus occurred at sympatric sites, and many of these individuals possessed allozymes diagnostic for both species in allopatry. Over 6% of the crayfish at one sympatric site were putative F 1 hybrids, 4% were putative F 2 individuals ( hybrid × hybrid origin), and 13% were putative backcrosses ( product of hybrid × parental matings). This is the first genetic documentation of hybridization between a resident and invading crayfish. Our results suggest that genetic mechanisms play a role in the extirpation of O. propinquus by O. rusticus and are consistent with observations of other researchers suggesting that hybridization with non‐native species is common among crayfishes at many other locations. High rates of endemism and widespread introductions of non‐native crayfish suggest that invasions and hybridization are a major threat to crayfish biodiversity.

Preface - Xianglin Shi; Vince Castranova; Val Vallyathan; William G. Perry (Molecular and Cellular Biochemistry, 2001)

Diapause in copepods (Crustacea) from ephemeral habitats with different hydroperiods in Everglades National Park (Florida, U.S.A.) - Maria Cristina Bruno; William F. Loftus; Janet W. Reid; Sue A. Perry (Hydrobiologia, 2001)

The effects of 10 days of spaceflight on the shuttle Endeavour on predominantly fast-twitch muscles in the rat - William J. Kraemer; Robert S. Staron; Scott E. Gordon; Jeff S. Volek; L. Perry Koziris; Noel D. Duncan; Bradley C. Nindl; Ana L. Gómez; James O. Marx; Andrew C. Fry; Jerry D. Murray (Histochemistry and Cell Biology, 2000)

Regional Differences in Intestinal Spreading and pH Recovery and the Impact on Salmon Calcitonin Absorption in Dogs - Yong-Hee Lee; Barbara A. Perry; John P. Sutyak; William Stern; Patrick J. Sinko (Pharmaceutical Research, 2000)

Edge distributions of Ceutorhynchus assimilis and its parasitoid Trichomalus perfectus in a crop of winter oilseed rape (Brassica napus) - A.K. Murchie; Ingrid H. Williams; J.N. Perry (BioControl, 1999)

Impact of Regional Intestinal pH Modulation on Absorption of Peptide Drugs: Oral Absorption Studies of Salmon Calcitonin in Beagle Dogs - Yong-Hee Lee; Barbara A. Perry; Stacy Labruno; Hee Sang Lee; William Stern; Lisa M. Falzone; Patrick J. Sinko (Pharmaceutical Research, 1999)

Biopharmaceutical Approaches for Developing and Assessing Oral Peptide Delivery Strategies and Systems: In Vitro Permeability and In Vivo Oral Absorption of Salmon Calcitonin - Patrick J. Sinko; Yong-Hee Lee; Vijaya Makhey; Glen D. Leesman; John P. Sutyak; Hongshi Yu; Barbara Perry; Curtis L. Smith; Peidi Hu; Erik J. Wagner; Lisa M. Falzone; Laura T. McWhorter; et al. (Pharmaceutical Research, 1999)

Response of soil and leaf litter microarthropods to forest application of diflubenzuron - William B. Perry; Tim A. Christiansen; Sue A. Perry (Ecotoxicology, 1997)

Changes in mutagenicity during crude oil degradation by fungi - Linda E. Rudd; Jerome J. Perry; Virginia S. Houk; Ron W. Williams; Larry D. Claxton (Biodegradation, 1996)